Comparison of the behavior of ZVI/carbon composites from both commercial origin and from spent Li-ion batteries and mill scale for the removal of ibuprofen in water. (15th June 2020) - Chen, Shuai; Li, Zixiang; Belver, Carolina; Gao, Guilan; Guan, Jie; Guo, Yaoguang; Li, Hui; Ma, Jiao; Bedia, Jorge; Wójtowicz, Patryk
Abstract: Zero valent iron/carbon composites were successfully synthesized from commercial iron oxide and graphite (ZVI/C) and also by using graphite obtained from spent Li-ion batteries and iron oxide from mill scale (ZVI/C-X) as a new approach for the valorization of these waste. The composites were synthesized through carbothermic reactions and tested as catalysts for the degradation of ibuprofen from water by Fenton reaction. The optimal conditions for synthesizing ZVI/C composites were a temperature of 1000 °C maintained for 2 h. The structural, and textural features of ZVI/C with different ZVI mass ratios were characterized by different techniques. ZVI/C composites with higher ZVI mass ratios showed higher degradation rates for the removal of ibuprofen both in presence and absence of H2 O2 . Moreover, ZVI/C-X composite, obtained from industrial waste, showed activity even after four consecutive cycles of use with very low concentration of iron ions in solution after reaction (4.8 mg L −1 after 4 h), which supports the high stability and low Fe-lixiviation of ZVI/C-X composite. The results of this study prove the possibility of synthesizing composites using graphite from spent Li-ion batteries and iron oxide from mill scale, and their potential for the degradation of ibuprofen in water, with comparable activities to those obtained from commercial feedstocks. Graphical abstract: Image 1 Highlights: ZVI composites were prepared from commercial and waste feedstocks by heating at 1000 °C for 2 h. ZVI particles were stably supported on rough graphite particles after carbothermic reaction. ZVI/C composites with high ZVI content achieved higher ibuprofen removal. ZVI/C-X has low cost compared with other catalysts for ibuprofen removal and comparable activity.